1993
DOI: 10.1103/physrevlett.71.448
|View full text |Cite
|
Sign up to set email alerts
|

Resonant x-ray Raman scattering in BKα emission spectra of boron oxide (B2O3

Abstract: The satellite structure for the B Ka emission spectrum of boron oxide has been elucidated by threshold experiments carried out by varying the excitation energy of the incident undulator beam from below the B K absorption edge to several tens of eV above the absorption edge. Prominent emission of the satellite peak was observed when the excitation energy was tuned to the narrow pre-edge peak in the absorption spectrum, corresponding to the transition from BOs) to an unoccupied antibonding pn* orbital. It is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Although the valence band emission region is slightly different for cBN and hBN, by far the most striking difference is the sharp feature at 193 eV from hBN. Similar features arising from emission above E F have been detected in other resonant SXF work from boroncontaining systems such as B 3 O 2 9 . It results from the anomalous inelastic x-ray scattering effect first discovered by Sparks.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Although the valence band emission region is slightly different for cBN and hBN, by far the most striking difference is the sharp feature at 193 eV from hBN. Similar features arising from emission above E F have been detected in other resonant SXF work from boroncontaining systems such as B 3 O 2 9 . It results from the anomalous inelastic x-ray scattering effect first discovered by Sparks.…”
supporting
confidence: 51%
“…[5][6][7][8][9] A valence emission spectrum results from transitions from valence band states to the core hole produced by the incident photons. In the nonresonant energy regime, the excitation energy is far above the core binding energy, and the absorption and emission events are uncoupled.…”
mentioning
confidence: 99%
“…Recently, SXES studies have been performed by means of the inelastic-light-scattering process using high-brilliance synchrotron radiation as an excitation light source. [1][2][3][4][5][6][7][8] Using synchrotron radiation, one can utilize the excitation energy dependence of the SXES, which provides an experimental method to understand the electronic structure of matters in relation to the band structure.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This is the resonant fluorescence or the inelastic lightscattering process, where the wave vector of the valence hole is the same as that of the excited electron. Thus, momentumresolved inelastic light scattering offers a band mapping technique.…”
Section: Introductionmentioning
confidence: 99%
“…The satellite structure in fluorescent x-ray emission spectra has recently been investigated by measuring selectively excited x-ray emission spectra [1][2][3][4]. We have demonstrated that the high-energy satellites in the B K x-ray emission spectra of boron oxide and boron nitride originate from resonant x-ray emissions due to an electron transition between boron 1s and unoccupied antibonding orbitals [5,6]. Prominent resonant x-ray emissions are observed in molecules with strongly localized unoccupied antibonding p ‫ء‬ orbitals, such as in boron atoms with threefold coordination.…”
mentioning
confidence: 99%